DIVA reagents for bovine tuberculosis vaccines in cattle. (July 2011) - Vordermeier, Martin; Jones, Gareth J; Whelan, Adam O
Significant progress has been made in the development of specific antigens that allow the differentiation of BCG-vaccinated and Mycobacterium bovis -infected cattle (the differential diagnosis of infected from vaccinated individuals test). This has been greatly facilitated by the completion of the genome sequences of Mycobacterium tuberculosis, M. bovis and BCG Pasteur and the application of comparative genome and transcriptome analysis to define differentiating infected from vaccinated animals (DIVA) antigens that complement the prototype DIVA antigens ESAT-6 and CFP-10. In this article we present an update of our current approaches including the search for stage-specific antigens, the identification of novel diagnostic biomarkers and the development of DIVA skin tests. We also discuss the possible cost-effective application of DIVA tests within the remits of a cattle BCG vaccine program.